Patchouli Oil Isolation and Identification of Chemical Components Using GC-MS - Souhoka, Fensia Analda; Al Aziz, Andi Zulkifli; Nazudin, Nazudin (Indonesian Journal of Chemical Research, 2020)
This research aims to isolate oil from patchouli (Pogostemon cablin Benth) and identify the chemical components of patchouli oil using Gas Chromatography-Mass Spectrometry (GC-MS). Patchouli plant samples were obtained from Welulu Village, Kolaka Regency, Southeast Sulawesi Province. Fresh patchouli leaves are dried in the sun for four days to a constant weight. Patchouli leaves water content is 77.41% (w/w). Dry patchouli leaves are distilled using the water and steam method for two hours. Water and oil distillates are separated using a separating funnel. Patchouli oil obtained was dried using Na2SO4 anhydrous and yield 0.73% (w/w). The results of GC-MS analysis showed that patchouli oil contained 13 chemical components compounds, namely Î²-patchoulene (4.56%), cedr-8-ene (1.24%), trans-caryophyllene (7.96%), Î±-guaiene (18.61%), seychellene (5.70%), patchoulene (2.88%), eremophilene (1.33%), azulene (8.74%), delta-guaiene (18.90%), cyclohexanone (1.10%), globulol (1.88%), veridiflorol (4.39%), and alcohol patchouli (22.7%).